PENGARUH SUPERVISI AKADEMIK BERBASIS TEKNOLOGI TERHADAP PENINGKATAN KINERJA GURU SMP NEGERI DI KECAMATAN BANTARKAWUNG - Atik Afwanudin, Muhammad; Apriani, Dewi; Kusrina, Tity (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the effect of technology-based academic supervision on the performance of public junior high school teachers in Bantarkawung District. Technology-based academic supervision was implemented through the use of digital media, particularly classroom learning video recordings created by teachers. This research employed a quantitative approach. The population consisted of 105 teachers, with 83 teachers selected as the research sample. Data were collected using questionnaires that had been tested for validity and reliability. Data analysis techniques included descriptive statistics, t-tests to examine partial effects, and F-tests to determine simultaneous effects. The results show that technology-based academic supervision has a positive and significant effect on teacher performance, as indicated by positive regression coefficients and significant t and F test results at a significance level of 0.05. These findings indicate that technology-based academic supervision can enhance the effectiveness of teacher professional development and support sustainable improvement in teacher performance